Foreign Direct Investment and the facilitation of circulation in Irish film production policy - Brodie, Patrick (Irish Journal of Arts Management and Cultural Policy, 2024)
This article argues that the ‘facilitation of circulation’ has come to shape Irish film industry policy, reflecting on correlations and developments across Screen Ireland and inward-investment agencies such as IDA Ireland. The financialisation of the media industries, along with structural changes in global film economies, has significant implications for workers and industrial formations on-the-ground in given places, nations, and regions. In treating film products as another commodity to be produced in a global assembly line, Screen Ireland has absorbed the industrial logics of what Kay Dickinson refers to as ‘supply chain cinema’ (2024). This article builds a political economic framework for analysing these transformations through a reflection on the Section 481 as an instantiation of their logics, brushing against the grain of mainstream media policy discourses towards a left critique of inward-investment-based screen policy.